Tradisi Kewajiban Anak Bungsu Tinggal Bersama Orang Tua Pasca Pernikahan dalam Adat Jawa: Analisis Maqashid Syariah dan Living Law - Pandu Irawan; Agus Setiawan; Ahmad Muslimin (CV. Bimbingan Belajar Assyfa, 2026)
This study analyzes the tradition of the youngest child's obligation to reside with parents after marriage in Javanese society, specifically in Kalirejo Village, Pesawaran Regency, employing the perspectives of Maqāṣid al-sharī'ah and living law. Employing a qualitative case study approach, this research collected data through observation, in-depth interviews, and documentation. The findings reveal that this tradition persists due to interconnected factors of family responsibility, economic considerations, inherited cultural values, and social pressure. From Eugen Ehrlich's perspective of living law, this tradition constitutes living law as it originates from social needs, is practiced collectively, and possesses strong social legitimacy, despite being dynamic and undergoing shifts. The Maqāṣid al-sharī'ah analysis utilizing Jasser Auda's systems approach demonstrates that the tradition contains benefits (maṣlaḥah) in preserving life (hifẓ al-nafs), lineage (hifẓ al-nasl), and realizing filial piety (birrul walidain). However, it also harbors potential for harm (mafsadah) in the form of unequal distribution of responsibilities and domestic conflict. The synthesis of both perspectives indicates that this tradition remains relevant provided it is reconstructed flexibly, justly, and based on family deliberation to achieve a balance between cultural values and Sharia principles.